Analytical Study of Heat Transfer under Effect of Internal Heat Generation and Radiation over a Stretching Surface - M. Almas (Journal of Advances in Applied & Computational Mathematics, 2015)
Homotopy Analysis Method (HAM) is used to analytically study the heat transfer in a porous medium over a stretching surface with internal heat generation and radiation. The governing equations are transformed into a system of ordinary differential equations and then solved using HAM method. Effects of different physical parameters such as permeability, suction, Prandtl number, radiation and Heat generation have been studied on temperature and velocity fields. And also analytical results have been shown for local skin friction coefficient and the Nusselt number. The analytical solutions have been compared with numerical results which showed remarkable agreements.